Dancing Through Time: Unveiling the Cultural Evolution of Cagayan de Oro’s Oro Higalaay Festival - Artazo, Alice; Tolod, Lourdes; Manaois, Jason (Journal of Interdisciplinary Perspectives, 2024)
This study investigates the historical background and cultural significance of the Higalaay Street Dancing, a central feature of the Higalaay Festival in Cagayan de Oro City, Philippines. Despite its importance as a cultural celebration, the festival, particularly the street dancing aspect, remains underexplored in existing scholarly literature. This research aims to fill that gap by focusing on the evolution of the Oro Higalaay Street Dance, tracing its transformation from its origins in the Kagayha-an Festival up to the 2023 Oro Higalaay Festival. The festival has grown to emphasize key historical, social, economic, and religious milestones, all honored through its vibrant street dancing tradition. Particularly, the festival pays tribute to St. Augustine, the patron saint of Cagayan de Oro, adding a significant religious dimension to the celebration. The research highlights how the festival has come to symbolize the city’s rich cultural and historical values, making it an important avenue for cultural preservation. The study employs a phenomenological research design within a qualitative framework, relying on in-depth interviews, audio recordings, and the transcription of local experiences to gain a deeper understanding of the festival’s impact. Through this approach, the study uncovers the role of street dancing not just as a form of entertainment but as a medium for preserving local traditions and fostering cultural pride among the people of Cagayan de Oro and its neighboring communities. The latest version of the street dance features a combination of religious and cultural elements in its choreography, music, attire, and thematic presentations. These elements allow audiences to connect more deeply with the city’s heritage while the dance becomes a powerful storytelling vehicle. Ultimately, this research enhances the understanding of the festival’s role in sustaining cultural identity and preserving traditions through the dynamic medium of dance.